Development of Interactive Video-Based Learning Media Combined with Blended Learning Method for Writing Short Story Materials in Elementary School - Dini, Rusfi Rama; Sumarni, Sri; Oktarina, Santi; Raharjo, Makmum (Universitas Sebelas Maret, 2024)
The creation of interactive video-based learning materials utilizing Adobe Animate CC 2022 was conducted and implemented in the context of the Indonesian language curriculum. This research aims to develop interactive video-based learning resources that are valid, practical, and effective for teaching short story writing. The development process followed the ADDIE model, which encompasses five phases: analysis, design, development, implementation, and evaluation. Evaluation methods included expert validation, one-on-one assessments, small group evaluations, and field tests. The findings indicated that the material's validity was rated at 90%, categorized as very valid; the media's validity was assessed at 87%, classified as highly valid; and the language component received a validity score of 88%, also deemed very valid. The average validity across the three assessments was 88%, falling within the very valid category. In terms of practicality, the one-on-one evaluation yielded a score of 86%, categorized as very practical, while the small group assessment achieved a score of 98%, classified as highly practical. The overall average practicality score was 92%, indicating a very hands-on approach. To assess media effectiveness, pretest results were 56%, while posttest results reached 96%, demonstrating significant learning outcomes for students, with an N-Gain score of 0.92. Consequently, the interactive video-based learning materials developed with Adobe Animate CC 2022 successfully engaged students and can be effectively utilized to enhance the Indonesian language curriculum, particularly in short story writing for fifth-grade elementary school students.